SEX DIFFERENCES IN METABOLIC CONTROL AND OBESITY - Sulaieva, O.N.; Belemets, N.I. (World of Medicine and Biology, 2017)
Obesity is considered as a risk factor for many diseases including diabetes mellitus, ischemic coronary diseases, osteoarthritis and cancer. In addition to genetic and environmental factors, style of life and physical activity, one of the important determinants of obesity and its complications development is sex dimorphism. It was shown that males and females are different in wide spectrum of parameters of metabolic control, principles and mechanisms of adipose tissue volume and distribution. Key basics of these differences are fundamental biological processes such as sex chromosomes and their genes. In four genotypes model it was shown number of X-chromosomes correlates with the risk of adiposity where as sex hormones are able to change this rule. Sex steroids play a crucial role in adipose tissue distribution and activity. It is well known that about 80% of fat is accumulated in subcutaneous adipose tissues at abdominal and gluteofemoral area, whereas visceral adipose tissue forms about 10-20% of entire fat. Interesting that in women fat accumulation in gluteofemoral zone, controlled by estrogens, is associated with low cardio-metabolic risk. However aging and menopause are accompanied with abdominal fat deposition and reshaping of woman’s body – so called shifting to android type of obesity. In addition to waist and visceral fat enlargement this results in prominent changes in glucose and lipid metabolism that increases the risk of cardio-metabolic complications. The current concept of sex-related fat distribution is based on estrogen and estrogen receptors (ER) role. Adipocytes express two types of estrogen receptors – ERα и ERβ. Knock-out of ERα gen in mice led to obesity due to visceral fat accumulation. The same features occur after gonadectomy, although estrogen administration of ovaryactomic animals resulted in decrease of visceral fat volume. It is widely accepted that estrogens play a protective role and decrease fat accumulation in visceral adipose tissue, and this effect is realized through ERα. In addition to peripheral effects, estrogen affects adipose tissue volume and functions through central regulation. The last effect is realized through modulation of sympathetic nervous system activity and results in regulation of lipolysis and thermogenesis. As far as the main sympathetic neurotransmitters are catecholamines, it was suggested that estrogen can modulate number and sensitivity of adrenoreceptors. In fact, adipocytes have both anti-lipolytic α2 and lipolytic β1-2-adrenoreceptors, which expression depends on sex hormones. In premenopausal females α2-adrenoreceptors prevail in subcutaneous fat that explains low lipolytic response of subcutaneous adipose tissue to epinephrine and norepinephrine. In contrast, β1-2 adrenoreceptors predominate in visceral adipose tissue of fertile females that can explain low fat accumulation and prevalence of lipolysis in this area. However males and females after menopause demonstrate reverse α2 to β1-2-adrenoreceptors ratio that leads to fat accumulation in visceral depot. In addition to this, sex differences include different ability to browning of adipose tissue that is associated with low adiposity and insulin tolerance, increase of adiponectin level and decrease steatosis in leptin-deficient animals. It was shown that females have more brown adipose tissues, and transformation of white adipocytes to brown is accelerated by estrogens. This is related with central effect of estrogens that accelerate sympathetic input on adipose tissue through β3-adrenoreceptors. In conclusion, sex steroids have diverse impact on adipose tissue plasticity and obesity mechanisms that is important to consider for development of the new strategy of obesity treatment and prophylactic, and for prediction of metabolic complications in males and females.